Wearable robotics : challenges and trends : proceedings of the 4th International Symposium on Wearable Robotics, WeRob2018, October 16-20, 2018, Pisa, Italy /: challenges and trends : proceedings of the 4th International Symposium on Wearable Robotics, WeRob2018, October 16-20, 2018, Pisa, Italy. ([2019]) - Unknown
No abstract available